A facile Synthesis of Quinoxaline–Oxadiazole Hybrids with Bis (1,2,3-triazole) Scaffolds Through Click Chemistry - Kuntla Krishnaveni; Banda Padma; Panaganti Leelavathi (The Bioscan, 2025)
In the present work, a modular synthetic approach based on click chemistry was employed to construct a novel series of bis(1,2,3-triazole)-linked quinoxaline–oxadiazole hybrids. The synthesis was accomplished via copper(I)-catalysed azide–alkyne cycloaddition (CuAAC), providing the target compounds in excellent yields with high regioselectivity. The structures of the synthesized hybrids were confirmed by IR, ¹H NMR, ¹³C NMR, mass spectrometry, and elemental analysis.